2020
DOI: 10.1186/s12348-020-00215-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of uveitis and macular edema among patients taking fingolimod 0.5 mg for multiple sclerosis

Abstract: Background Patients with multiple sclerosis (MS) have a higher incidence of uveitis compared with the general population. Fingolimod, a first line disease modifying drug used in multiple sclerosis, may cause macular edema and thus requires ophthalmic examination. However, murine models and anecdotal reports suggest fingolimod may reduce the incidence of uveitis. Purpose To report the incidence of uveitis and macular edema among those on fingolimod 0.5 mg (Gilenya®) therapy for multiple sclerosis (MS). Meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…FT, despite well-tolerated in MS patients, has several side effects including macular edema, lymphopenia, hypertension and more commonly increased liver enzymes (6,18,19). In the present study, we retrospectively evaluated the effect of FT on liver enzyme levels (ALT and GGT) in RRMS patients and observed that both ALT and GGT were increased in the patients.…”
Section: Discussionmentioning
confidence: 85%
“…FT, despite well-tolerated in MS patients, has several side effects including macular edema, lymphopenia, hypertension and more commonly increased liver enzymes (6,18,19). In the present study, we retrospectively evaluated the effect of FT on liver enzyme levels (ALT and GGT) in RRMS patients and observed that both ALT and GGT were increased in the patients.…”
Section: Discussionmentioning
confidence: 85%
“…[64] Ayrıca, topikal kortikosteroidler ve NSAİİ'ler, intravitreal triamsinolon, oral karbonik anhidraz inhibitörlerinin etkili olduğunu bildiren ayrı ayrı çalışmalar vardır. [70,71] Fingolimod kullanan MS hastalarında gelişen makuler ödemin ilaç kullanımına bağlı olarak mı yoksa MS ile ilişkili üveite sekonder mi geliştiği iyi ayırt edilerek tedavi buna göre düzenlenmelidir. [63,64] Sonuç Kistoid makuler ödem, ağrısız görme kaybının önemli bir sebebidir.…”
Section: Epinefrinunclassified